Correlation between neutrophil-to-high-density lipoprotein cholesterol ratio (NHR) and adverse prognosis in patients who achieve complete recanalization after thrombectomy for acute large vessel occlusion stroke - Ci, Shunchao; Li, Di; Wang, Feng; Li, Ke; Yin, Lin (Frontiers in Neurology, 2025)
BackgroundThe neutrophil-to-high-density lipoprotein cholesterol ratio (NHR) has emerged as a novel inflammatory marker with prognostic significance. This study aims to explore the association between NHR and adverse prognosis in patients with acute large vessel occlusion (LVO) stroke who achieved complete recanalization after mechanical thrombectomy (MT).MethodsThis retrospective study analyzed acute ischemic stroke (AIS) patients with LVO who underwent MT at three stroke centers in Dalian, China, between January 2016 and November 2023. Complete recanalization was defined as achieving a modified Thrombolysis in Cerebral Infarction (mTICI) grade 3. Blood parameters were assessed within 24 h after MT. We compared intergroup differences based on NHR tertiles and employed the multivariate logistic regression analysis to assess the relationship between NHR and adverse outcomes.ResultsThis study included 348 AIS patients with LVO, of whom 215 (61.8%) had adverse clinical outcomes at 90 days. The multivariate logistic regression analysis revealed a significant association between an elevated NHR and 90-day adverse outcomes (OR 2.311, 95% CI 1.248–4.278, p = 0.008). A restricted cubic spline curve demonstrated a linear dose–response relationship between NHR and adverse outcomes, with a p-value of 0.348 for non-linearity.ConclusionOur findings revealed that an elevated NHR could increase the risk of adverse prognosis following complete recanalization after MT in acute LVO stroke patients, which indicated that NHR could serve as a potential inflammatory marker for identifying high risk patients.